Emergence of Virtual Currencies-Study of Cryptocurrency in Digital Marketing - Minky Sharma (International Journal of Islamic and Social Sciences (ISOS), 2021)
Present economic scenario is the subject of innovations in all aspect of economy like banking marketing and trade. Digital innovation facilitates the settlement of transactions without presence of individual since virtual currency has also emerged in the way of innovations which facilitate the trading and investment alternatives to the people. Concept of Virtual Currency: Virtual currency or money is a type of unregulated virtual/digital currency which is issued/managed by developers and largely accepted by the members of a virtual community. Definition: According to European Banking Authority (2014), virtual currency is a digital representation of value that is not issued by a banking authority or a public authority, nor essentially attached to a fiat currency, but is accepted by natural or legal persons as a means of payment and can be transferred, stored or traded electronically". It can be collected, stored and transferred among stakeholders. This currency is not subject to any kind of monetary or fiscal policy. Some currencies having the features of crypto currency while some currencies are not holding the features of crypto currency.